Genetic parameters including the service sire effect for the sow traits stillbirth and piglet losses in Czech Large White and Landrace - Wolf, J.; Wolfová, M. (Czech Journal of Animal Science, 2012)
Genetic parameters including the proportion of variance for the service sire effect were estimated for number of piglets stillborn (including piglets died until 24 h after birth) and number of piglets died from 24 h after birth until weaning in Czech Large White (89 231 litters) and Czech Landrace (28 320 litters) pigs. Both traits were considered to be traits of the sow. Two two-trait animal models were evaluated for each breed including or excluding the service sire effect. Estimates of genetic parameters were very similar for the two models. The heritability for number of stillborn piglets was 0.06 in both breeds and both models and the heritability for number of piglets died until weaning was 0.07 in Czech Large White and 0.05 to 0.06 in Czech Landrace. The proportion of variance due to service sire was very low (between 0.8 and 1.6%). Therefore, there is no need to include the service sire effect in models for genetic evaluation. A selection against farrowing losses is recommended though only a slow improvement of the trait can be expected. Selecting against piglets died until weaning seems to be cumbersome. Probably a selection on number of piglets weaned could be helpful in minimizing piglet losses until weaning.
Keywords: pig; reproduction